Synthesis and Antibacterial Activity of 1-Hydro-5-methyl-6 (Substituted Phenylhydrazono)-4-Pyrazolin-7-ones - RAJPUT, A.P.; RAJPUT, S.S. (Asian Journal of Chemistry, 2010)
Various 1-hydro-5-methyl-6 (substituted phenylhydrazono)-4- pyrazolin-7-ones were synthesized in two steps using moderate conditions and evaluated for their antibacterial activity.